Reporting like there was no pandemic: Cultural journalism during the COVID-19 pandemic in Finland, Sweden, and Latvia - Maarit Jaakkola; Skulte, Ilva (MedieKultur: Journal of media and communication research, 2023)
The 2020 COVID-19 outbreak led to business closures and social activity restrictions. In par-ticular, the cultural sector was severely hit by lockdowns, placing cultural journalism within exceptional circumstances. In this article, we analyse how journalists overcame restrictions by developing a proactive approach to the cultural sphere. As cultural journalism largely leans on the coverage of pre-planned events, exploring the journalistic approaches employed during the pandemic may unveil essential factors in the cultural-journalistic concept of culture and country differences. Our data comprise three consecutive sample weeks from 2020–2021 (weeks 17, 47, and 15) from the culture pages of the largest dailies of Finland, Sweden, and Latvia. Through comparative content analysis, we investigated the journalistic strategies of cultural desks. Using a story entity as the unit of analysis, we exam-ined three aspects of story ideation: reliance on pseudo-events, choice and development of cultural–journalistic genres, and staging and storytelling methods regarding newsroom proactivity. We found differences in cultural concepts, including (dis)connections between art and society, which are frequently discussed in the literature. The results further indicate that proactivity can be a useful tool for developing future cultural journalism.